Natural products as novel anti-obesity agents: insights into mechanisms of action and potential for therapeutic management - Shaik Mohamed Sayed, Ummul Fathima; Moshawih, Said; Goh, Hui Poh; Kifli, Nurolaini; Gupta, Gaurav; Singh, Sachin Kumar; Chellappan, Dinesh Kumar; Dua, Kamal; Hermansyah, Andi; Ser, Hooi Leng; Ming, Long Chiau; Goh, Bey Hing (Frontiers in Pharmacology, 2023)
Obesity affects more than 10% of the adult population globally. Despite the introduction of diverse medications aimed at combating fat accumulation and obesity, a significant number of these pharmaceutical interventions are linked to substantial occurrences of severe adverse events, occasionally leading to their withdrawal from the market. Natural products serve as attractive sources for anti-obesity agents as many of them can alter the host metabolic processes and maintain glucose homeostasis via metabolic and thermogenic stimulation, appetite regulation, pancreatic lipase and amylase inhibition, insulin sensitivity enhancing, adipogenesis inhibition and adipocyte apoptosis induction. In this review, we shed light on the biological processes that control energy balance and thermogenesis as well as metabolic pathways in white adipose tissue browning, we also highlight the anti-obesity potential of natural products with their mechanism of action. Based on previous findings, the crucial proteins and molecular pathways involved in adipose tissue browning and lipolysis induction are uncoupling protein-1, PR domain containing 16, and peroxisome proliferator-activated receptor-γ in addition to Sirtuin-1 and AMP-activated protein kinase pathway. Given that some phytochemicals can also lower proinflammatory substances like TNF-α, IL-6, and IL-1 secreted from adipose tissue and change the production of adipokines like leptin and adiponectin, which are important regulators of body weight, natural products represent a treasure trove for anti-obesity agents. In conclusion, conducting comprehensive research on natural products holds the potential to accelerate the development of an improved obesity management strategy characterized by heightened efficacy and reduced incidence of side effects.